2017
DOI: 10.1002/admt.201700003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Performance and Stability of Perovskite Nanocrystal Light‐Emitting Diodes with a Polymer Matrix

Abstract: efficiency (EQE) values of the devices have increased from 0.12% to 3.8% for green emission and to 5.7% for red emission. [10][11][12][13][14][15][16][17][18] Recently, bulk film-based perovskite LEDs have been reported to reach high EQEs of 8.53% for green emission and 11.7% for near-infrared emission; however, the issues of long-term device stability and photoluminescence (PL)/electroluminescence (EL) blinking emission should be resolved before the commercial application of these materials can be realized. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
0
31
1
Order By: Relevance
“…To date, although numerous efforts have been made to achieve water-stable perovskite micro- and nano-particles with low dimension (0D, 1D and 2D),4a,7,9,13 most are focused on the external encapsulation of metal oxides,14,15 polymers,16,17 mesoporous inorganic oxides18,19 and metal–organic framework20 matrixes. Only recently, Han's and Yang's groups demonstrated that pyridine additives with various alkyl-chain substituents or alkyl ammonium cations on the perovskite surface can substantially improve the stability of perovskite solar cells 21,22.…”
Section: Resultsmentioning
confidence: 99%
“…To date, although numerous efforts have been made to achieve water-stable perovskite micro- and nano-particles with low dimension (0D, 1D and 2D),4a,7,9,13 most are focused on the external encapsulation of metal oxides,14,15 polymers,16,17 mesoporous inorganic oxides18,19 and metal–organic framework20 matrixes. Only recently, Han's and Yang's groups demonstrated that pyridine additives with various alkyl-chain substituents or alkyl ammonium cations on the perovskite surface can substantially improve the stability of perovskite solar cells 21,22.…”
Section: Resultsmentioning
confidence: 99%
“…CsPbI 3 perovskite can easily lose its structural integrity under humidity or under UV illumination, leading to decomposition or unwanted phase transformation from cubic to orthorhombic phase 3d,4. Considerable efforts have thus been devoted to improve stability of perovskite QDs, such as adding encapsulation using silica, silica spheres, mesoporous silica or polyhedral oligomeric silsesquioxanes, coating by lipid layers, fabrication of AlO x ‐passivated perovskite QD films by atomic layer deposition, and protection within hydrophobic phosphate glasses and polymethyl methacrylate polymer . However, such insulating coatings would also hinder the charge transport between QDs, leading to poor conductivity of such embedded perovskite QD films.…”
Section: Introductionmentioning
confidence: 99%
“…Many literatures have demonstrated that the morphology of the emission layer determines the performance of device. [80][81][82] Improper processing methods will bring about the clustering of nanocrystal and lead to the rough thin film, which deteriorates not only the optical performance but also long-term stability of the device [83] (Figure 2A). On the one hand, this may result in a turn-on voltage (Von) much higher than the band gap energy of the nanocrystals, suggesting that poor contact between the functional layers and the carrier injection from chargetransporting layers (CTL) into nanocrystals was inefficient.…”
Section: Rough Morphology Of the Emission Layermentioning
confidence: 99%